Linguistic, cultural and axiological study of English and Uzbek spoken communication - Abdulboqiyeva Gulbahor Shodmonali qizi, Odilova Gulchiroy Xusniddin qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In the process of globalization, communication between different cultures is increasing. This makes it important to study the linguocultural and axiological aspects of the verbal communication of different languages. Linguocultural studies studies the interaction between language and culture, and axiology studies the system of values. Linguistic barriers play a significant role in intercultural communication. Identifying and learning how to overcome these barriers is essential for effective intercultural communication.Linguistic barriers and their causes Linguistic barriers arise from language and speech differences that arise in communication between representatives of different cultures. These barriers can be related to the following factors: • Language proficiency: The lack of sufficient knowledge of each other's language by the communication participants. • Speech styles: The differences in speech styles across cultures. • Cultural codes: Cultural codes embedded in language and their different interpretations.